Peningkatan Kompetensi Perawat Dalam Merespon Kebutuhan Pasien Difabel Di Kota Pontianak - Hanafi, Hanafi; Pramana, Yoga; Fahdi, Faisal Kholid; Maulana, M Ali (Jurnal Pengabdi, 2025)
Abstract:  This community service activity involves nurses who are members of the Indonesian National Nurses Association in the Pontianak city area. This activity involves collaboration and cooperation with several partners, including the Pontianak City PPNI Regional Representative Council (DPD), students who are members of the Nursing Science Student Association (HIMIKAWA), as well as resource persons from the Pontianak City Regional Indonesian Sign Language Center (PUSBISINDO). The activity will be carried out in September 2024. This activity will be carried out by providing socialization on the introduction of sign language to nurses. This community service activity was carried out on September 21 2024 with a total of 30 participants attending. The activity method was carried out by measuring the participants' skills before being given sign language assistance provided by WBDC and evaluating the skills again after the assistance was carried out. The material and introduction to sign language were delivered directly by professional presenters, namely from the West Boneo Deaf Community (WBDC), starting from training participants on how to demonstrate the alphabet, letters A to Z and numbers as well as training participants on how to carry out simple conversations, how to carry out initial assessments using sign language starting from name, age, complaints when in health services.Keywords: Pusbisindu, Danger Signals, Skills